Assinaturas de AGN e outflow em galáxias Red Geyser com observações do GMOS-IFU - Ilha, Gabriele da Silva (2023)
We present an analysis of gas ionisation and kinematics for nine Red Geysers selected from the MaNGA (Mapping Nearby Galaxies at Apache Point Observatory) survey of SDSS-IV (Sloan Digital Sky Survey-IV) and observed with the GMOS (Gemini Multi-Object Spectrographs) integral field unit (IFU) from the Gemini North telescope. Red Geysers are quiescent galaxies with galactic scale ionised outflows, likely due to low-luminosity Active Galactic Nuclei (AGN). The GMOS-IFU observations were obtained for the nuclear region of these galaxies in the inner ∼1–3 kpc. The main goals of this work are the investigation of the gas ionisation source and the presence of biconical outflows originating in a precessing accretion disc in Red Geyser galaxies. The emission-line ratios suggest the presence of Seyfert/LINER (LowIonisation Nuclear Emission Region) nuclei in all sources. Two galaxies show Hα equivalent width (Hα EW) larger than 3 Å (indicative of AGN ionisation) within an aperture 2.5′′ of diameter (1.3–3.7 kpc at the distance of galaxies) for MaNGA data, while with the higher resolution GMOS data, four galaxies present Hα EW> 3 Å within an aperture equal to the angular resolution (0.3–0.9 kpc). For two objects with GMOS-IFU data, the Hα EW is lower than 3 Å but larger than 1.5 Å, most probably due to a faint AGN. The spatially resolved electron density maps show values between 100–3000 cm−3 and are consistent with those determined for the NLR (Narrow-Line Region) and outflows in other studies. The [N II]λ6583 emission-line profiles are asymmetrical for the six galaxies with extended emission, with blue wings on the redshifted side of the velocity field and red wings on the blueshifted side. A biconical outflow can cause these asymmetries. The large (MaNGA) and the nuclear scale (GMOS-IFU) gas velocity fields are misaligned, with a kinematic position angle difference between 12◦–60◦ determined using the FIT KINEMATICS PA method and 13◦–49◦ when calculated the mean value of radial profiles of the kinematic position angle. Furthermore, the variation of radial profiles of the kinematic position angle with distance from the nuclear region is continuous when we combine the values determined from the GMOS-IFU and MaNGA velocity fields. Besides that, the observed variation in the kinematic position angle is consistent with outflows originating in a precessing accretion disc as proposed for the Akira galaxy, the prototype of the Red Geyser class. Thus, our results support previous indications that the gas in Red Geysers is ionised by an AGN, at least in their central region, with the presence of outflows, likely originating in a precessing accretion disc.